Fundamentals of equilibrium and steady-state thermodynamics - Tschoegl, Nicholas W., 1918- (Elsevier Science, 2000)
This book summarizes the salient features of both equilibrium and steady-state thermodynamic theory under a uniform postulatory viewpoint. The emphasis is upon the formal aspects and logical structure of thermodynamic theory, allowing it to emerge as a coherent whole, unfettered by much of those details which - albeit indispensable in practical applications - tend to obscure this coherent structure. Largely because of this, statistical mechanics and reference to molecular structure are, barring an occasional allusion, avoided. The treatment is, therefore, 'classical', or - using a perhaps more appropriate word - 'phenomenological'. The volume almost exclusively deals with 'ideal' systems, given that the treatment of 'real' systems properly belongs in the realm of applied, rather than theoretical thermodynamics. For these reasons, only selected ideal systems are covered. Ideal gases are discussed extensively. The ideal solution is treated as an example of a liquid system. The amorphous ideal rubber serves as an example of a solid. The formalism developed in these sections is a model for the treatment of other, more complex systems. This short structural overview is written in the hope that a knowledge of steady-state theory will deepen readers' understanding of thermodynamics as a whole.